Impact of CD44/326 peritoneal cells as response indicators in advanced gastric cancer patients receiving repeated intraperitoneal perfusion normothermic chemotherapy - Odilon de Souza Filho; Reinaldo Rondinelli; Antônio Carlos Acetta; Sérgio Bertolace; Alexandre Palladino; Cristiano Duque Guedes; Claudia Cristine Rocha Vieira; Luis Claudio Santos Thuler; Claudia Diniz; Everton Cruz dos Santos; Eliana Abdelhay (Therapeutic Advances in Medical Oncology)
Background: In gastric cancer (GC), the dissemination of neoplastic cells (NCs) in the peritoneal cavity is related to disease progression and poor prognosis. Elimination of NC through chemotherapy is needed to achieve better outcomes before conversion surgery. Objectives: The objective of this study was to evaluate the impact of NC CD44+/CD326+ levels through flow cytometry (FC) on peritoneal lavage (PL) fluid as a response indicator for conversion surgery. Methods: Patients with GC and NCs in the peritoneal cavity with or without peritoneal carcinomatosis (PC) and ascites were evaluated via minimally invasive staging. The PLs of patients were analyzed by FC to quantify NCs. All patients were treated with repeated intraperitoneal perfusion normothermic chemotherapy (RIPPENC). Patients who had negative NCs or reduced NCs were referred for conversion surgery. Results: Thirty patients were enrolled in this study and divided into three groups. In the first group, 20 patients with positive cytology (C+) and/or PC with a PC index (PCI) ⩽6 were treated with RIPPENC. Otherwise, six patients with C+ and PC with a PCI >7 and four patients with C+, ascites, and a PCI ranging from 15 to 22 were treated with palliative RIPPENC. The percentage of CD44+/CD326+ cells was correlated with the number of RIPPENC cycles and resections. The median follow-up time was 14.8 months. The overall median survival since the first RIPPENC was 14.6 months among those who did not undergo resection and 22.6 months among those who underwent resection ( p  = 0.001). Moreover, we observed a correlation between the percentage of CD44+/CD326+ cells in the PL region and patient survival. Conclusion: The use of FC to identify PL CD44+/CD326+ cell levels may be an important innovative biomarker for determining the presence of NCs, directly affecting the success of RIPPENC for conversion surgery.